The Use Of Forensic Linguistics In Assessing The Truth Of The Accused's And Witnesses' Perspective MaqÄá¹£id As-Syar'iyyah - Amaliah, Rizky; Zulkarnain, Zulkarnain (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
The goal of law in Islam is to achieve the welfare of humanity. One of the ways to support the realization of justice is the use of forensic linguistics to assess the truth of testimony from defendants and witnesses in court. However, Indonesian legislation does not yet mandate the use of forensic linguistics in criminal cases. This study aims to analyze the application of maqÄá¹£id as-syar'iyyah in the use of forensic linguistics to assess the truth of testimony from defendants and witnesses. This is a normative legal research with a qualitative approach, focusing on primary data from the Indonesian Penal Code (KUHP) and court decisions that apply forensic linguistics methods. Data analysis was conducted using deductive reasoning based on the theory of maqÄá¹£id as-syar'iyyah. The findings show that the use of forensic linguistics to assess the truth of testimony from defendants and witnesses in criminal cases is part of the maslahat dharuriyyat. In particular, cases related to religion, murder, and corruption are crucial areas of maslahat dharuriyyat. Therefore, the presence of linguistic expert witnesses in court proceedings is an inevitability to ensure true justice.